Dual-functional injectable adhesive hydrogel delivering ginger-derived doxorubicin vesicles for osteosarcoma recurrence suppression and post-resection wound healing - Zhang, Qiang; Zhang, Yu; Chen, Hui; Sun, Lei-Na; Zhang, Bin; Yue, Dong-Sheng; Wang, Chang-Li; Zhang, Zhen-Fa (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionElderly osteosarcoma patients often face significant postoperative challenges, including high recurrence rates and delayed wound healing. These issues are primarily due to inadequate hemostasis, reactive oxygen species (ROS)-mediated microenvironmental inhibition, and compromised bone regeneration. This study aims to address these challenges by introducing a multifunctional adhesive hydrogel designed for synergistic therapy.MethodsThe hydrogel consists of carboxymethyl chitosan methacryloyl (CMCSMA) and tannic acid (TA), which form a dynamic, crosslinked polymer network capable of rapid tissue adhesion and adaptability to moist wound environments. The hydrogel incorporates ginger vesicles (GVs) loaded with doxorubicin (DOX), offering a dual therapeutic approach. The system facilitates hemostasis through physical barrier formation and activation of coagulation factors, while GVs and DOX provide controlled release for ROS scavenging, reduction of inflammation, and targeted tumor cell elimination.ResultsIn vitro experiments demonstrated the hydrogel’s ability to efficiently remove ROS and promote osteogenic differentiation. In a rat osteosarcoma resection model, the hydrogel significantly shortened hemostasis time compared to conventional sponges, reduced tumor recurrence, and accelerated wound healing.DiscussionThis study presents a multifunctional hydrogel that combines hemostasis, antioxidation, tissue repair, and recurrence prevention. The findings suggest that this integrated therapeutic approach holds substantial potential for clinical application in elderly osteosarcoma treatment, addressing critical postoperative challenges and improving patient outcomes.